OPTIMALISASI PEMANFAATAN LAHAN GAMBUT MELALUI USAHA PERTANIAN PRODUKTIF UNTUK MENCIPTAKAN EKONOMI DESA YANG BERKELANJUTAN - Utomo, Medea Rahmadhani; Qurbani, Indah Dwi; Hakim, Muhammad Lukman; Kamal, Muhammad Arif; Margaretha, Fransiska; Syaharini, Dessyta Miranda (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Limited human resources and technology trigger the risk of non-optimal use of peatlands. Excessive use of peatlands also encourages land destruction, which is characterized by a decrease in the production function of agricultural products. Excessive economic orientation makes farmers sometimes unable to control sustainable peatland management. However, not all farmers understand that environmental sustainability leads to local economic productivity. From this case, through this study, several objectives emerged, namely knowing the natural potential and characteristics of peatlands in Jambi province. Identifying types of agricultural commodities that can be optimized for peatland use. Also find ways to manage agricultural waste that can be used as an added value for local communities. Some of this information can be obtained through a qualitative research approach with qualitative descriptive analysis. The term optimization has not been understood as environmental balance so it is still translated as land intensification that tends to damage peatlands. The most important productive agricultural business is liberica coffee commodities. Likasih coffee is a characteristic of Jambi's agricultural symbol. Other potential crops include coconut, watermelon, cucumber, and rice. Some of these agricultural businesses indirectly encourage farmers to manage sustainable agricultural businesses. At the same time, it reduces the motivation of palm oil businesses that tend to be exploitative. In addition, agricultural waste, which has not been utilized so far, is well managed by farmers. The processed waste is an added value for the people of Jambi Province